2020
DOI: 10.3389/fphar.2019.01485
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Evaluation on the Pharmacokinetics of Platinum-Based Anticancer Drugs From Animal to Cell Level: Based on Total Platinum and Intact Drugs

Abstract: Cisplatin, carboplatin, and oxaliplatin are the common platinum-based anticancer drugs widely used in the chemotherapeutic treatment of solid tumors in clinic. However, the comprehensive pharmacokinetics of platinum-based anticancer drugs has not been fully understood yet. This leads to many limitations for the further studies on their pharmacology and toxicology. In this study, we conduct a systemic evaluation on the pharmacokinetics of three platinum analogues at animal and cell levels, with quantification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Moreover, we found large individual and gender differences in platinum levels, perhaps related to polymorphisms of the GSTP1 and XRCC1 genes, and drug metabolic diversity in vivo (Sawers et al, 2014;Gu et al, 2015). Our finding is consistent with prior research showing that the elimination time for platinum is more than 25 times that for the intact platinum-based drug in the rat (Qin et al, 2019). In addition, there was an increasing trend over the first three time points, which reflected the platinum accumulation.…”
Section: Platinum Accumulationsupporting
confidence: 92%
“…Moreover, we found large individual and gender differences in platinum levels, perhaps related to polymorphisms of the GSTP1 and XRCC1 genes, and drug metabolic diversity in vivo (Sawers et al, 2014;Gu et al, 2015). Our finding is consistent with prior research showing that the elimination time for platinum is more than 25 times that for the intact platinum-based drug in the rat (Qin et al, 2019). In addition, there was an increasing trend over the first three time points, which reflected the platinum accumulation.…”
Section: Platinum Accumulationsupporting
confidence: 92%
“…As illustrated in Table 7 , the pharmacokinetic behavior of total platinum in plasma from free L-OHP, L-OHP bare lip, and L-OHP PEG lip compiled with the two-compartment model, characterized by a biphasic exponential decay with an initial rapid phase followed by a slower elimination terminal phase (Figures 6(b) – 6(d) ). The prolonged terminal elimination phase presumably represents inactive platinum complexes that were formed through chemical reactions with low molecular weight nucleophiles [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that after intravenous infusion, L-OHP is mainly identifiable in three compartments, plasma-bound platinum, ultrafiltrate plasma platinum, and erythrocyte-bound platinum [ 19 ]. The ultrafiltrate platinum contains the intact drug and the low molecular weight platinum metabolites, which are generally known to be the main active ingredients, whereas platinum bound to plasma proteins or erythrocytes is considered to be pharmacologically inactive [ 10 , 20 ]. Intact L-OHP was completely eliminated from blood circulation after 2 h of its intraperitoneal injection to rats [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin is one of the most potent chemotherapeutic regimens that is widely used for the treatment of various types of solid tumor, including head and neck cancer, in clinical practice ( 36 , 37 ). However, its clinical efficiency is limited by chemoresistance and side effects, which includes mainly nephrotoxicity and bone marrow toxicity ( 29 , 38 ).…”
Section: Discussionmentioning
confidence: 99%